2022
DOI: 10.34312/jmathedu.v3i2.15604
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Model Pembelajaran Probing Prompting Terhadap Hasil Belajar Siswa Pada Materi Segiempat

Abstract: This article discusses the Effect of the Probing Prompting Learning Model on Students’ Learning Outcomes in a Rectangular topic to know the differences in learning outcomes of students whose learning uses the Probing Prompting Learning Model and learning outcomes of students whose learning uses the direct Learning Model in Rectangular topic. The method used is an experimental design with a pretest-posttest control group design. The sampling technique used cluster random sampling and the technique of data colle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 3 publications
0
4
0
2
Order By: Relevance
“…Additionally, this study examined the enhancement of mathematical concept understanding by implementing the probing prompting learning model. Swasono et al (2014) conducted research supporting the notion that the probing prompting learning model can effectively enhance students' grasp of mathematical concepts. The improvement in students' mathematical understanding is evident from their achievement in essential competencies, as depicted in Figure 2.…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…Additionally, this study examined the enhancement of mathematical concept understanding by implementing the probing prompting learning model. Swasono et al (2014) conducted research supporting the notion that the probing prompting learning model can effectively enhance students' grasp of mathematical concepts. The improvement in students' mathematical understanding is evident from their achievement in essential competencies, as depicted in Figure 2.…”
Section: Resultsmentioning
confidence: 94%
“…This is consistent with Muna and Afriansyah (2018), who suggested that mathematical understanding can be improved through learning models aligned with students' cognitive development. One such model considered effective in enhancing students' ability to understand mathematical concepts is the probing prompting model (Swasono et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hasil belajar merujuk pada tingkat keberhasilan yang dicapai oleh seseorang setelah usaha tertentu atau pencapaian akademis siswa melalui ujian, tugas, pertanyaan aktif, atau indikator lain yang digunakan sebagai kriteria skor hasil belajar [6] [7]. Pembelajaran yang berhasil adalah pembelajaran yang mendorong kreativitas siswa secara keseluruhan, meningkatkan partisipasi aktif, mencapai tujuan pembelajaran secara efektif, berlangsung dalam lingkungan yang menyenangkan, dan berpengaruh pada hasil belajar siswa yang digunakan untuk menentukan sejauh mana pemahaman dan penguasaan siswa terhadap materi pembelajaran [8].…”
Section: Pendahuluanunclassified
“…Berdasarkan analisis data hasil penelitian diatas diperoleh rata-rata hasil posttest untuk kelas eksperimen adalah 80,97 dan untuk kelas kontrol adalah 75,18 (Swasono, Suyitno, & Susilo, 2014). Hal ini menunjukkan bahwa nilai rata-rata hasil belajar kelas eksperimen yang diajarkan dengan model pembelajaran Probing Prompting lebih tinggi dari rata-rata hasil belajar kelas kontrol yang diajarkan dengan model pembelajaran Discovery learning.…”
Section: Kesimpulanunclassified